Business environment and business climate of MSMEs in the city of María Auxiliadora (Journal on studies and research of academic knowledge, 2021)
This research describes the business environment and business climate of Small and Medium Enterprises in the City of María Auxiliadora. The study of the problem leads to a local analysis of business strategies, as well as external factors determining business activity. This work was carried out using a non-experimental, basic and descriptive research methodology with a qualitative-quantitative nature. The analysis showed the poor accessibility of entrepreneurs to the credit systems for MSMEs, as well as the deficient training of the productive sectors of the area, the segmentation of business activity, differentiating it from the sale of goods and services, as well as the low applicability of business strategies.
Keywords: Companies; Environment; Business Climate; Sustainability; Competitiveness